2018
DOI: 10.1371/journal.pone.0193249
|View full text |Cite
|
Sign up to set email alerts
|

Subtype assignment of CLL based on B-cell subset associated gene signatures from normal bone marrow – A proof of concept study

Abstract: Diagnostic and prognostic evaluation of chronic lymphocytic leukemia (CLL) involves blood cell counts, immunophenotyping, IgVH mutation status, and cytogenetic analyses. We generated B-cell associated gene-signatures (BAGS) based on six naturally occurring B-cell subsets within normal bone marrow. Our hypothesis is that by segregating CLL according to BAGS, we can identify subtypes with prognostic implications in support of pathogenetic value of BAGS. Microarray-based gene-expression samples from eight indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Interestingly, analyzing the publicly available dataset GSE94669, we found that out of the most significant MyD88 L265P -upregulated genes, CD44, BATF, LGALS3, and NFKBIZ exhibited an expression pattern specific to ABC DLBCL cell lines, with the highest expression in ABC DLBCL cell lines bearing the L265P mutation. We also identified the same expression pattern in a mouse lymphoma model of mutant MyD88 ( Figure S6 ; dataset GSE141453 [ 147 ]) and other available lymphoma datasets (not shown; e.g., GSE50721 [ 148 ], GSE56315 [ 149 , 150 ], and GSE31312 [ 151 ]). Since literature evidence supports the important roles of CD44, BATF, LGALS3, and NFKBIZ in cancer, we decided to validate the expression of these genes with independent experimental methods.…”
Section: Discussionsupporting
confidence: 61%
“…Interestingly, analyzing the publicly available dataset GSE94669, we found that out of the most significant MyD88 L265P -upregulated genes, CD44, BATF, LGALS3, and NFKBIZ exhibited an expression pattern specific to ABC DLBCL cell lines, with the highest expression in ABC DLBCL cell lines bearing the L265P mutation. We also identified the same expression pattern in a mouse lymphoma model of mutant MyD88 ( Figure S6 ; dataset GSE141453 [ 147 ]) and other available lymphoma datasets (not shown; e.g., GSE50721 [ 148 ], GSE56315 [ 149 , 150 ], and GSE31312 [ 151 ]). Since literature evidence supports the important roles of CD44, BATF, LGALS3, and NFKBIZ in cancer, we decided to validate the expression of these genes with independent experimental methods.…”
Section: Discussionsupporting
confidence: 61%
“…The precise cellular origin of CLL remains unclear and the current knowledge of CLL biology demonstrates no direct link between the proliferative circulating CLL cells to a specific normal B-cell subset [ 46 , 47 ]. B-cell associated gene-signatures are separated based on pre- and post-GC B-lymphocytes (pre GC: pre-BI, pre-BII, and immature; post GC: naïve, memory, or plasma cell subtypes) [ 47 , 48 ]. Several lines of evidence have suggested that BCL6 and BACH2 cooperate in GC B-cells [ 49 , 50 , 51 ], thus understanding the clinical significance of such transcriptional regulators in CLL patients and the protein networks influenced by them is of high importance in CLL treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated the prognostic value of BAGS in chronic lymphocytic leukemia, with elevated mutation frequencies of specific subtypes and distinct predicted responses to treatment depending on subtype. 21 In other B-cell-like malignancies, such as follicular lymphoma and Burkitt lymphoma, the BAGS subtypes may provide additional important information to explain clinical heterogeneity. The BAGS2Clinic makes this information accessible for a low price and short turnaround time to help explain some of the molecular and prognostic heterogeneity observed in DLBCL.…”
Section: Discussionmentioning
confidence: 99%